‘We got more than we expected.’ Older people’s experiences of falls-prevention exercise interventions and implications for practice; a qualitative study - Lafond, Natasher (Prim Health Care Res Dev, 2019)
AIM: To explore the experiences of older adults participating in strength and balance exercise programmes and understand participants’ rationale for programme uptake and completion. BACKGROUND: Regular physical activity, specifically strength and balance exercises, has been shown to improve health and well-being and reduce the risk of falling in older adults. With the number of people living into older age increasing, understanding older people’s experiences of strength and balance programmes and what encourages their take-up and completion is extremely important. This paper reports on the qualitative experiences of older adults that previously participated in ProAct65+, a randomised controlled trial of Falls Management Exercise (FaME) programme and Otago Exercise Programme (OEP) versus usual care. METHODS: Ten general practices in Nottinghamshire and Derbyshire, England, who participated in the ProAct65+ trial were approached to take part. Using maximum variation sampling (age, gender, falls history, fear of falling and trial arm) we recruited, via the practices, 30 people that had participated in the FaME (n = 15) or OEP (n = 15) trial arms. Participants were interviewed in their own homes. Interviews were audio-recorded, transcribed verbatim and thematically analysed. FINDINGS: We identified five themes: choice of exercise programme; commitment, discipline and motivation; benchmarking, feedback and monitoring; benefits of the exercise programmes and reactions to the end of the programmes. There were four sub-themes within the benefits theme: pleasure and boredom, social interaction and isolation, physical benefits, and knowledge and understanding. This study has outlined the experiences and identified specific barriers and facilitators to uptake and completion of falls-prevention exercises by older adults. The perspective and experiences of these participants is important if programmes are to be designed to meet the needs of the target population. Insights from this study will enable commissioners to develop and provide appropriate falls-prevention exercise programmes that encourage high uptake and programme completion.